Commission civile. Au nom de la République. Léger-Félicité Sonthonax, commissaire-civil de la République, délégué aux Isles françaises de l'Amérique sous le vent, pour y rétablir l'ordre et la tranquilité publique, a tous les Français de Saint-Domingue - Sonthonax, Léger Félicité, 1763-1813; Polverel, Etienne, 1738-1794; La Salle d'Offémont, Adrien Nicolas Piédefer, marquis de, 1735-1818 (De l'Imprimerie de François Lamotte, 1793)
This proclamation, written by Sonthonax on behalf of himself as well as Etienne Polverel, his fellow Commissaire civil, defends his decision, based upon the rights of man, to make African slaves and all their descendants free. Special mention is given to Adrien-Nicolas Lasalle, who disagreed with Sonthonax and begged permission of the English to emigrate, and whom Sonthonax calls "imbecille". An excerpt of a letter written by Lasalle to Sonthonax and dated Au Cap 30 août 1793, appears in the second column.